Design of Carbon Dioxide Levels Measurement in Human Expiration Using EtCO2 Capnography Method - Rifky Maulana Fuadi; Endro Yulianto; Bambang Guruh Irianto; Abhishek Mishra (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
Asthma is a chronic respiratory disease and has become the main reason patients are always rushed to the hospital emergency department. Capnography is a new method for examining asthma by measuring CO2 levels released by the lungs. The aim of this research is to create an EtCO2 capnography device that is able to measure CO2 levels in patients with asthma or difficulty breathing to assist doctors in determining the urgency of using a ventilator in a patient. The EtCO2 Capnography device used in the hospital uses a sensor that is expensive, but in this study, a CO2 gas sensor type Cozir-WX-20 is used at a low price. The research was conducted by utilizing a CO2 gas sensor type Cozir-WX-20 which reads CO2 concentration in ppm value and a microcontroller as an analog to digital data processor to be displayed on the LCD. Sensor characterization was carried out to compare the side-stream and main-stream methods, response time readings, and the accuracy of the cozir sensor. The resulting data is taken from CO2 cylinders and medical air gas at various flow volume values and is connected to the Cozir sensor and EtCO2 main-stream patient monitors and side-stream EtCO2 patient monitors. The resulting CO2 readings from CO2 tubes and medical water on the Cozir-WX-20 sensor and main-stream patient monitors get an error of 4.6%, namely at a CO2 concentration of 7% or 70,000 ppm and sensor accuracy is above 95%. As for the side-stream method, the reading error is 1.96% and 1.74% at a CO2 concentration of 6-7%. Sensor accuracy on the side-stream method cozir module is above 95%. Response time reading CO2 gas at a concentration of 1%-7% under 5 seconds. It is hoped that this inexpensive EtCO2 Capnography device can be used for diagnostic purposes in the emergency room or intensive care unit to quickly and accurately determine the urgency of using a ventilator in a patient to avoid a fatal condition.